The sensitivity of marine N2 fixation to dissolved inorganic nitrogen - Knapp, Angela (Frontiers in Microbiology, 2012)
The dominant process adding nitrogen (N) to the ocean, di-nitrogen (N2) fixation, is mediated by prokaryotes (diazotrophs) sensitive to a variety of environmental factors. In particular, it is often assumed that consequential rates of marine N2 fixation do not occur where concentrations of nitrate (NO3-) and/or ammonium (NH4+) exceed 1 µM because of the additional energetic cost associated with assimilating N2 gas relative to NO3- or NH4+. However, an examination of culturing studies and in situ N2 fixation rate measurements from marine euphotic, mesopelagic, and benthic environments indicates that while elevated concentrations of NO3- and/or NH4+ can depress N2 fixation rates, the process can continue at substantial rates in the presence of as much as 30 µM NO3- and/or 200 µM NH4+. These findings challenge expectations of the degree to which inorganic N inhibits this process. The high rates of N2 fixation measured in some benthic environments suggest that certain benthic diazotrophs may be less sensitive to prolonged exposure to NO3- and/or NH4+ than cyanobacterial diazotrophs. Additionally, recent work indicates that cyanobacterial diazotrophs may have mechanisms for mitigating NO3- inhibition of N2 fixation. In particular, it has been recently shown that increasing phosphorus (P) availability increases diazotroph abundance, thus compensating for lower per-cell rates of N2 fixation that result from NO3- inhibition. Consequently, low ambient surface ocean N:P ratios such as those generated by the increasing rates of N loss thought to occur during the last glacial to interglacial transition may create conditions favorable for N2 fixation and thus help to stabilize the marine N inventory on relevant time scales. These findings suggest that restricting measurements of marine N2 fixation to oligotrophic surface waters may underestimate global rates of this process and contribute to uncertainties in the marine N budget.